CRITICAL DISCOURSE ANALYSIS ON THE COVID-19 TOPIC AT THE 2020 USA FINAL PRESIDENTIAL DEBATE - Atiqah Elfannur Rahmah; Mardliya Pratiwi Zamruddin; Setya Ariani (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2021)
This article analyzes the COVID-19 topic discussed at the 2020 USA final presidential debate. The purpose of this research is to describe the effect of the discourses on the socio-cultural practices. The approach employed in this research is the three-dimensional critical discourse analysis by Norman Fairclough consisting of text analysis, discursive practice analysis, and socio-cultural practice analysis of the discourses. The discourses of the COVID-19 topic are seen as important by the American citizens because they need clarity of how their future president would fight the pandemic in their term. The result of this research shows that the two discourses by the presidential candidates produced distinctive depictions of COVID-19. Discourse produced by Donald Trump offered a more optimistic view regarding the COVID-19 situation in the United States, while Joe Biden’s discourse gave a more pessimistic view towards the COVID-19 situation. The presidential candidates provided different views of the COVID-19 situation in the United States in order to appeal and convince the American citizens into voting them. The different depictions of COVID-19 situation in the United States resulted in the American citizens expressing their disappointment over Donald Trump’s optimism which also extend to the criticism towards the White House, while praised Joe Biden’s pessimism on the topic. Ultimately, the discourses are seen as unsatisfactory by the American citizens due to their inability to give details and elaborations on the plan to fight against COVID-19 in the next four years. Lastly, these discourses might create and instil indecisiveness in the American citizens’ voting decision.